LAVESI-FIRE simulation output at Lake Satagay, Central Yakutia, Siberia - Glückler, Ramesh; Kruse, Stefan (Zenodo, 2023)
Simulation output data for long-term fire-vegetation simulations with the individual-based, spatially explicit model LAVESI-FIRE. The individual, numbered simulation foldersaredescribed in the included .docx file, as well as in the related research paper (submitted). In each folder, following files can be found (_18224XX refers to the climate input used for the simulation): datatrees_currencies_18224 XX .csv : Timeseries data. Simulation area-wide summarized data on tree abundance, climate, environment and fire occurrence. Each row of the table represents an individual annual simulation timestep. databiomassgrid_1_18224 XX _ XX 00_1_ X .csv : Spatial data. Each file includes tree abundancefor one species (_1 = Larix gmelinii _2 = Larix sibirica _3 = Larix cajanderi _4 = Picea obovata _5 = Pinus sylvestris _6 = Pinus sibirica ), summarized in grid cells with x- and y-coordinates. datatrees_Treedensity XX 00_18224 XX .csv : Spatial data. Each file includes tree density, environment, and fire occurrence,summarized in grid cells with x- and y-coordinates. For more detail, please refer to the research paper: Glückler et al.: Simulating wildfire impacts on boreal forest structure over the past 20,000 years since the Last Glacial Maximum in Central Yakutia, Siberia(submitted - DOI will be added once available)